Pathways to Sustainability in Sub-Sahara Africa : Are Institutional Quality Levels Subservient in Achieving Green GDP Growth? - Appiah, Michael; Onifade, Stephen Taiwo; Gyamfi, Bright Akwasi (Springer, 2024)
There is a growing need for a transition to green economic growth (GGDP) given that the current economic system is largely environmentally unsustainable. This study thus addresses GGDP enhancement in less developed countries using the case of Sub-Sahara Africa (SSA) countries where institutional deficiencies are typically at the root of most resource depletion and environmental degradation issues. Six institutional quality measures were used namely corruption control, government effectiveness, political stability, regulatory quality, rule of law, and voice of accountability while controlling for other factors like industrialization, energy use, and population growth in the region. The study applied a battery of second-generation panel econometric techniques in the empirical analysis after which both Bootstrap Quantile regression (BQR) technique and panel ordinary least squares (OLS) estimation approaches were applied to observe the variables' roles on GGDP advancement in SSA. From the findings, corruption control and government (policy) effectiveness favorably impact Green GDP in SSA. However, both rule of law and regulatory quality performed poorly as they were insignificant to GGDP enhancement. Furthermore, all control variables promote GGDP except for population growth. Thus, the findings buttress the need to strengthen institutions for effective governance and quality environmental regulations to enhance GGDP growth towards actualizing sustainable development goals (SDGs) in the SSA region.
Keywords: Green GDP; Institutional quality; Sustainability; Sub Sahara Africa; fi=Taloustiede|en=Economics|